Environmental distribution and seasonal dynamics of Marteilia refringens and Bonamia ostreae, two protozoan parasites of the European flat oyster, Ostrea edulis - Mérou, Nicolas; Lecadet, Cyrielle; Ubertini, Martin; Pouvreau, Stéphane; Arzul, Isabelle (Frontiers in Cellular and Infection Microbiology, 2023)
Marteilia refringens and Bonamia ostreae are protozoan parasites responsible for mortalities of farmed and wild flat oysters Ostrea edulis in Europe since 1968 and 1979, respectively. Despite almost 40 years of research, the life-cycle of these parasites is still poorly known, especially regarding their environmental distribution. We carried out an integrated field study to investigate the dynamics of M. refringens and B. ostreae in Rade of Brest, where both parasites are known to be present. We used real-time PCR to monitor seasonally over four years the presence of both parasites in flat oysters. In addition, we used previously developed eDNA based-approaches to detect parasites in planktonic and benthic compartments for the last two years of the survey. M. refringens was detected in flat oysters over the whole sampling period, sometimes with a prevalence exceeding 90%. It was also detected in all the sampled environmental compartments, suggesting their involvement in parasite transmission and overwintering. In contrast, B. ostreae prevalence in flat oysters was low and the parasite was almost never detected in planktonic and benthic compartments. Finally, the analysis of environmental data allowed describing the seasonal dynamics of both parasites in Rade of Brest: M. refringens was more detected in summer and fall than in winter and spring, contrary to B. ostreae which showed higher prevalence in winter and spring. The present study emphasizes the difference between M. refringens and B. ostreae ecology, the former presenting a wider environmental distribution than the latter, which seems closely associated to flat oysters. Our findings highlight the key role of planktonic and benthic compartments in M. refringens transmission and storage or potential overwintering, respectively. More generally, we provide here a method that could be useful not only to further investigate non cultivable pathogens life-cycle, but also to support the design of more integrated surveillance programs.